Studies in the life-cycle of human amoebiasis: from its protozoological, morbid, & clinical aspects (illustrated) - Moses, John Gregory Owen (The University of Edinburgh, 1917)
The Prognosis of Liver abscess cases, either with or without attendant complications, self-induced or otherwise, therefore depends almost entirely upon the Method of Treatment employed. As has been mentioned before, and which the detailed cases emphasise , the clinical condition. of the patient is sometimes less important than the measures employed for their alleviation. The most important consideration is the exhibition of Ipecacuanha in full doses or its alkaloid Emetin subcutaneously, in the pre-suppurative stage of an Acute Hepatitis. Other factors which will influence the Iortality rate e.g, the presence of complications when the case first comes under treatment, the number of abscesses present their position, size & sterility, will be described under Prognosis. The Tables arranged have been chosen to illustrate the mortality aspect from every point of view, and though. the Commentary Notes appear rather as a criticism of post - operative treatment, than actually reviewing the gross mortality rates, yet mortality rate is essentially wrapped up with the question of Open Operation, and the less heroic procedures. Evacuation through the three routes have been compared and contrasted as influencing profoundly the mortality rate. Such clinical facts as have been presented by Rogers, have been gathered together and re- quoted; so that the gross figures themselves should be co- related with the clinical state of the patients, so that some index may accompany the dull recital of bare figures, and have a direct bearing upon what has been termed "The General & Surgical Mortality following Liver Abscess ". In some cases of spontaneous evacuati on taking place into the Bowel or through the lungs, spontaneous cure results, so that Nature's methods of evacuating amoebic abscesses of the liver, are frequently entirely successful in curing the patient, while they are far less often accompanied by the extension of serious inflammation to the Pleura or Peritoneum, or septic infecti on of the abscess cavity, than are the Surgeon's attempts in the same direction (Rogers). Any method of treatment must always be governed by the clinical condition and an appreciation of the pathological state, combined with the reaction of the system against such state.